Correlation of the environmental consciousness of kazakhstanis due to the pandemic (Herald of Journalism, 2021)
The topic of the research is devoted to the study of changes in the environmental consciousness of Kazakhstanis in connection with the pandemic. The text of the study answers to such questions like how does the massive use of social networks in a pandemic affect the nature of the perception of information and the further reaction of users to events.The aim of the study is to show how social networks are moving away from the role of a tool. And its conceptualization is already shown as an aggregator of public opinion in techno-cultural relations. Accordingly, this article examines the tendency of changing the environmental consciousness of Kazakhstanis during a pandemic.The scientific significance of the study lies in the topic itself, the importance and role of social networks in the formation of the main trends and themes were determined. Findings were done by studying the main platform for the dissemination of environmental ideas - the social network Instagram. The article used research methods such as interviews, as well as empirical research methods such as observation and comparison (in social networks). The research was helped by such qualities and advantages of Instagram as hashtags (#airpollution, #plasticpollution #кобейтуз), popular news that were in the rank of the most discussed and sent to other users. As part of the study, interviews were conducted with the owners of the recycling business.The article discusses the hypothesis that during the pandemic, activity on social networks increased significantly, which led to an intensive discussion of environmental topics in Kazakhstan.This work has an important research component and can be assessed by experts in the field of public opinion research, as well as this article can be a learning base for students and novice specialists.Key words: ecology, youth, social networks, ecological consciousness, pandemic.